KI 2011: advances in artificial intelligence 34th annual German conference on AI, Berlin, Germany, October 4-7,2011, proceedings - Bach, Joscha; Edelkamp, Stefan (Lecture notes in computer science, 2011)
This book constitutes the  refereed proceedings of the 34th Annual German Conference on Artificial Intelligence, KI 2011, held in Berlin, Germany, in October 2011. The  32 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 81 submissions. The papers are divided in topical sections on computational learning and datamining, knowledge representation and reasonings, augmented reality, swarm intelligence; and planning and scheduling